Evolutionary computation in combinatorial optimization : 16th European Conference, EvoCOP 2016, Porto, Portugal, March 30- April 1, 2016, Proceedings /: 16th European Conference, EvoCOP 2016, Porto, Portugal, March 30- April 1, 2016, Proceedings. (2015) - Unknown
No abstract available